Does the preoperative mild renal dysfunction effect mortality and morbidity following valve cardiac surgery? - Hadi Abo Aljadayel; Hussein AlKanj; Salah Koja; Fadi Butruss (Indian Heart Journal, 2016)
Aims: The objective of this study was to investigate the effect of preoperative mild renal dysfunction (RD), not requiring dialysis, on mortality and morbidity after valve cardiac surgery (VCS). Population: We studied 340 consecutive patients (2008–2012), who underwent VCS with or without coronary artery bypass graft (CABG). Methods: Preoperative RD was calculated with the abbreviated Modification of Diet in Renal Disease formula and was defined as a glomerular filtration rate <60 ml/min/1.73 m2. Logistic regression analysis was used to assess the effect of preoperative renal dysfunction (RD) on operative and adverse outcomes. Results: 80 patients (30%) had preoperative mild RD. Patients with preoperative RD were older, had a higher rate of preoperative anemia (43% vs. 25%, p < 0.001), and more comorbidities. Patients with preoperative RD had worse outcomes with more reoperation (6.8% vs. 2.3%, p < 0.001). Conclusion: Preoperative RD was significantly and independently associated with more red blood cell transfusions and longer hospital stay (median 9 vs. 8 days, p < 0.001). Mortality was similar in both groups (3.4% vs. 2.3%, p = 0.43). Preoperative mild RD in patients undergoing cardiac valve surgery is an independent marker of postoperative morbidity.